Peran Pasar Tradisional Tapen dalam Mendukung Aktivitas Ekonomi Masyarakat di Desa Tapen Kecamatan Kudu Kabupaten Jombang - Salsa Andrawati; Masruchan Masruchan (ARZUSIN, 2026)
Although traditional markets have received attention in various studies, research that specifically discusses the multidimensional role of traditional markets in supporting community economic activities, including distribution, employment, income, fulfillment of needs, and social interaction simultaneously, remains limited. This study aims to analyze the role of Tapen Traditional Market in supporting the economic activities of the community of Tapen Village, Kudu Subdistrict, Jombang Regency. This study used a qualitative approach with a case study design, involving 22 informants consisting of large and small traders, employees, rice distribution agents, active buyers, the market head, the village head, and parking attendants, who were selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that Tapen Market performs five main interrelated roles, namely distributing basic necessities through rice agent networks and the wholesale networks of two large traders, absorbing more than 200 workers, creating daily economic circulation that increases the income of large and small traders, providing basic necessities at affordable prices through a bargaining mechanism, and serving as a space for social interaction that strengthens the cohesion of village residents. The conclusion of this study affirms that social capital and local distribution networks play an important role in maintaining the resilience of traditional markets amid the expansion of modern retail and e-commerce. The implications of this study provide theoretical contributions to the development of economic sociology and people’s economy theory, as well as practical implications for village governments and market managers in designing gradual digitalization and improving market infrastructure.